Global Mental Health and systems of diagnostic classification: clinical and cultural perspectives - Alarcón, Renato D. (Acta Bioethica, 2016)
Historical and conceptual aspects of Global Health and Global Mental Health are examined and topics such as resources, professional and social attitudes toward mental disorders, the multidimensional experience of getting ill and the presence of world systems of psychiatric diagnosis and classification, are reviewed. The application of these areas of knowledge in medical practice require the integrated use of clinical and socio-cultural perspectives whose precise alignment is an essential component of accurate diagnoses, successful treatments and a consistent improvement of mental health as a component of public health. The latter includes preventive measures applicable to general populations, communities and health care proper. Management of socio-cultural aspects of diagnosis and treatment is imperative as is that of the growing relationship between mental health and neurosciences. The operationalization of this series of interactive processes must be part of legislations which, in turn, can make training, research and dissemination of the resulting data, possible.